2004
DOI: 10.1038/sj.jea.7500390
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radiofrequency exposure from cellular telephone daily use in an epidemiological study: German Validation study of the international case–control study of cancers of the brain—INTERPHONE-Study

Abstract: Objective: The objective of the study is to validate self-reported cellular phone use information by comparing it with the cumulative emitted power and duration of calls measured by software-modified cellular phones (SMP). The information was obtained using a questionnaire developed for the international case-control study on the risk of the use of mobile phones in tumours of the brain or salivary gland (INTERPHONE-study). Method: The study was conducted in Bielefeld, Germany. Volunteers were asked to use SMPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 8 publications
9
48
0
Order By: Relevance
“…Reports of past mobile phone use are subject to random error, as recall even in the short term has been shown to be inaccurate. [26][27][28][29] Over-reporting of the amount of mobile phone use by 50-100% has been common. This is likely to attenuate any true relationship between exposure and outcome, and it might distort dose-response.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of past mobile phone use are subject to random error, as recall even in the short term has been shown to be inaccurate. [26][27][28][29] Over-reporting of the amount of mobile phone use by 50-100% has been common. This is likely to attenuate any true relationship between exposure and outcome, and it might distort dose-response.…”
Section: Discussionmentioning
confidence: 99%
“…phone mainly in the city had no effect on estimates of the cumulative power by the number of calls (Berg et al, 2005). Similarly, an Italian study found that the difference between urban and rural areas was quite small, whereas the factors stationary-moving and outdoor-indoor were more predictive of the average power emitted by the mobile phones (Ardoino et al, 2004).…”
Section: Uk: Proportion Of Time 2wmentioning
confidence: 92%
“…In brain tumour studies, cases may also recall exposure with greater random error, as the tumour may affect their memory. Previous validation studies have shown substantial error in healthy volunteers' short-term recall of phone use (Parslow et al, 2003;Samkange-Zeeb et al, 2004;Berg et al, 2005;Morrissey, 2007;Vrijheid et al, 2006a;Hours et al, 2007b). However, there is as yet no direct evidence of differential recall error in studies of mobile phone use and brain tumours.…”
Section: Introductionmentioning
confidence: 99%